A Rare Tumor of The Oral Mucosa, Myopericytoma: Case Report - Candan Semra Paksoy; Mert Özlü; İpek Atak; Elif Polat (Ankara University, 2022)
Myopericytoma (MPC) is defined as a benign mesenchymal neoplasm consisting mostly of oval spindle-shaped myoid-like cells with perivascular growth. Apart from being a rare lesion in all anatomical regions of the body, it is extremely rare in the oral and maxillofacial region and only a limited number of cases have been reported in the literature. We present here the case of MPC in a 42-year-old female patient who had a painless, enlarging lesion in the anterior mandible. Intraoral examination of the lesion revealed a smooth, nonwhite, pedunculated, fibrotic, painless, and nonbleeding lesion in the lingual aspect of the anterior mandible. Histopathologic examination revealed a tumor consisting of spherical/nodular structures composed of spindle cells and hemangioperistomatous vascular structures in the form of staghorn. These tumor cells showed no signs of malignancy. On immunohistochemical examination, the tumor cells were positive for CD34 and SMA. SMA Protein was also focally positive in nodular structures formed by spindle cells and tumor stroma. S-100 protein was negative in the lesion. To our knowledge, this is the second case of MPC that occurred in the mandibular gingiva.